Evaluating carbon and water fluxes and stocks in Brazil under changing climate and refined regional scenarios for changes in land use - Castro, Aline Anderson de; von Randow, Celso; von Randow, Rita de Cássia Silva; Bezerra, Francisco Gilney Silva (Frontiers in Climate, 2022)
Climate change and land use change can alter the role of natural vegetation as a sink or source of atmospheric carbon. In this work, we evaluate the response of water and carbon fluxes and stocks in Brazilian biomes as a proxy for ecosystem services of regional climate regulation under two contrasting future scenarios: a sustainable development scenario, where some deforested areas are restored by vegetation regrowth combined with a low representative concentration pathway, and a pessimistic scenario, where there is still high deforestation rates and strong climate change. We used refined regional scenarios for land use change in Brazil, together with climate projections of the HADGEM2-ES model for RCPs 2.6 and 8.5 to drive a land surface model and assess possible future impacts in the surface fluxes. Our results show that drying climate and shifts of natural vegetation into anthropogenic land use might shift part of upper story biomass into understory biomass, which can be more vulnerable to dry events. The simulations also show that climate change appears to drive most of the water balance change compared to land use change, especially over the Amazon.